2022
DOI: 10.1017/jfm.2022.770
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and spectral characteristics of information flux between turbulent boundary layers and porous media

Abstract: The interaction between boundary layer turbulence and a porous layer is the cornerstone of interface engineering. In this study, the spatial and spectral-resolved transfer entropy is used to assess the asymmetry of the causal interaction next to the permeable wall. The analysis is based on pore-resolved direct numerical simulation of turbulent channel flow over cylinder arrays. The spatial map of transfer entropy reveals the information flux between the porous medium and arbitrary nearby positions, and paths c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…The K Br condition was obtained using linear stability analysis of permeable wall boundary conditions derived using the Darcy-Brinkman equation but remain applicable to the pore-scale resolved DNS data in this study, indicating that the microstructure details of the porous substrates do not have a leading-order impact on the instability. This agrees with the argument made by White & Nepf (2007), who assessed that only the overall resistance of the porous layer is important and not the details of its geometry in bringing about and sustaining the instability.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The K Br condition was obtained using linear stability analysis of permeable wall boundary conditions derived using the Darcy-Brinkman equation but remain applicable to the pore-scale resolved DNS data in this study, indicating that the microstructure details of the porous substrates do not have a leading-order impact on the instability. This agrees with the argument made by White & Nepf (2007), who assessed that only the overall resistance of the porous layer is important and not the details of its geometry in bringing about and sustaining the instability.…”
Section: Discussionsupporting
confidence: 91%
“…arrays of cylinders serving as models for vegetation canopies. White & Nepf (2007) demonstrated that the coherent motion at the top of the arrays exhibited a single dominant frequency which was the same as that in free shear layers subject to K-H instability. They therefore characterized the flows as being similar to mixing layers where the instability originates at the inflection point of the mean velocity profile inside the porous region.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations